Clinical Governance to Enhance User Involvement in Care: A Canadian Multiple Case Study in Mental Health - Nathalie Clavel; Marie-Pascale Pomey (International Journal of Health Policy and Management, 2022)
BackgroundIndividuals with serious mental illness face challenges in managing their health, leading to the need for integrating their needs and preferences in care decisions. One way to enhance collaboration between users and providers is to improve clinical governance; a shared responsibility between managers and providers, supported by healthcare organizations (HCOs), policies, and standards. We applied the concept of clinical governance to understand (1) how managers and providers can enhance the involvement of users in mental health, (2) the contextual and organizational factors that facilitate user involvement in care, and (3) the users’ perceptions of their involvement in care. MethodsWe conducted two, in-depth case studies from two clinical teams in Canada offering outpatient care for users with acute mental illness. A total of 25 interviews were carried out with managers, and four focus groups were held with providers. A measure of patient-reported experience was used to evaluate the users’ perceptions of their involvement in care. ResultsThe providers used two methods to involve users in the care planning process: encouraging users to identify their life goals and supporting them to define recovery-oriented objectives. To encourage the adoption of collaborative practices, the managers used various practices such as revising care protocols, strengthening providers’ knowledge of best practices and integrating peer-support workers (PSWs) in the team. Compliance with organizational and external commitments/requirements for user involvement, access to specific training and the institutionalization of a culture promoting user involvement facilitated the adoption of collaborative practices. We found that mental health teams that adopt recovery and collaborative practices with users show a high degree of user-perceived involvement in care. ConclusionThis is the first study to apply the concept of clinical governance to understand how managerial and clinical practices, and other organizational and contextual factors, can enhance the involvement of mental healthcare users.